The influence of autistic symptoms on social and non-social cognition and on real-life functioning in people with schizophrenia: Evidence from the Italian Network for Research on Psychoses multicenter study. Issue 1 (10th November 2020) - Vita, Antonio; Barlati, Stefano; Deste, Giacomo; Rocca, Paola; Rossi, Alessandro; Bertolino, Alessandro; Aguglia, Eugenio; Amore, Mario; Bellomo, Antonello; Biondi, Massimo; Carpiniello, Bernardo; Collantoni, Enrico; et al.
Abstract: Background: Autism spectrum disorders (ASDs) and schizophrenia spectrum disorders (SSDs), although conceptualized as separate entities, may share some clinical and neurobiological features. ASD symptoms may have a relevant role in determining a more severe clinical presentation of schizophrenic disorder but their relationships with cognitive aspects and functional outcomes of the disease remain to be addressed in large samples of individuals. Aims: To investigate the clinical, cognitive, and functional correlates of ASD symptoms in a large sample of people diagnosed with schizophrenia. Methods: The severity of ASD symptoms was measured with the PANSS Autism Severity Scale (PAUSS) in 921 individuals recruited for the Italian Network for Research on Psychoses multicenter study. Based on the PAUSS scores, three groups of subjects were compared on a wide array of cognitive and functional measures. Results: Subjects with more severe ASD symptoms showed a poorer performance in the processing speed ( p  = 0.010), attention ( p  = 0.011), verbal memory ( p  = 0.035), and social cognition ( p  = 0.001) domains, and an overall lower global cognitive composite score ( p  = 0.010). Subjects with more severe ASD symptoms also showed poorer functional capacity ( p  = 0.004), real-world interpersonal relationships ( p  < 0.001), and participation in community-living activities ( p  < 0.001). Conclusions: These findings strengthen the notion that ASD symptoms may have a relevant impact on different aspects of the disease, crucial to the life of people with schizophrenia. Prominent ASD symptoms may characterize a specific subpopulation of individuals with SSD.